Effectiveness of a service learning model with Allied Health Assistant students in aged care. (3rd May 2016) - Zulch, Debbie; Saunders, Rosemary; Peters, Judith; Quinlivan, Julie
Abstract : This paper explores the impact of a student learning activity involving service learning. As part of a vocational course in the Academy of Health Sciences at a Western Australian TAFE (Technical and Further Education) institute, Allied Health Assistant (AHA) students participated in a service learning program focused on work-based learning in residential aged care. Students delivered a therapy program for residents at the facility, and then completed evaluation questionnaires on conclusion of the study. Of 121 students completing the questionnaires, 91% thought the experience challenged their way of thinking, while only two percent disagreed. The majority of students (93%) reported the experience interesting and engaging and a similar percentage (93%) reported that they felt better prepared to enter the workforce. The major themes in qualitative analysis related to the positive learning experience, increased confidence for future working career, improved knowledge and practice of aged care, and improved resident and student quality of life.